The effect of elderly exercise on sleep quality - Afgani, Apen; Lesmana, Sandi; J Callista, Agsel (ACTA Medical Health Sciences, 2024)
An elderly person will begin to experience changes in various aspects. The most frequently complained health problem among the elderly is nighttime sleep disturbances. Exercise is known to help improve sleep quality in the elderly. This study aims to examine the effect of exercise on sleep quality among elderly individuals at the Kota Batu Public Health Center, Bogor Regency. The research method used was cross-sectional. The research sample consisted of 27 respondents, obtained through random sampling, and included elderly individuals who actively participated in regular exercise programs at the health center. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The sleep quality scores were analyzed using the independent t-test, and the group comparison between individuals who engaged in regular exercise and those who did not was conducted using the Mann-Whitney test. The results showed that the majority of the elderly had good sleep quality (59%). A total of 14 respondents (52%) regularly exercised. There was a significant difference in sleep quality between those who regularly exercised and those who did not, with significant differences observed in the components of subjective sleep quality (p=0.007), sleep latency (p=0.019), sleep disturbances (p=0.021), and daytime dysfunction (p=0.002). This study found a significant effect of exercise on sleep quality among the elderly at the Kota Batu Public Health Center, Bogor Regency, with a p-value < 0.05 (p=0.00). This indicates a significant effect of elderly exercise on sleep quality in the elderly at the Kota Batu Public Health Center, Bogor Regency DOI : 10.35990/amhs.v3n2.p84-90 REFERENCES Kementerian Kesehatan Republik Indonesia. (2022). Infodatin Lanjut Usia (Lansia). Pusat Data dan Informasi, Kementerian Kesehatan Republik Indonesia, p. 12. Badan Pusat Statistik Kabupaten Bogor. (2021). Statistical Report. Subekti, R. T., & Nina, R. (2022). The impact of exercise on sleep quality in the elderly. Jurnal Kesehatan Panca Bhakti Lampung, 10(September 2021), 110–120. Rezaei, M., Khormali, M., Akbarpour, S., Sadeghniiat-Hagighi, K., & Shamsipour, M. (2018). Sleep quality and its association with psychological distress and sleep hygiene: A cross-sectional study among pre-clinical medical students. Sleep Science, 11(4), 274. Retrieved from https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6361305/ Harisa, A., Syahrul, S., Yodang, Y., Abady, R., & Bas, A. G. (2022). Analysis of factors affecting sleep quality in elderly patients with chronic diseases. Jurnal Kesehatan Vokasional, 7(1), 1. Miasa, N. W. N. P., Wibawa, A., Widnyana, M., & Dewi, N. N. A. (2020). The relationship between elderly exercise and sleep quality among seniors in Badung Regency. Sport and Fitness Journal, 8(3), 158. Barrett, B., Harden, C. M., Brown, R. L., Coe, C. L., & Irwin, M. R. (2020). Mindfulness meditation and exercise both improve sleep quality: Secondary analysis of a randomized controlled trial of community-dwelling adults. Sleep Health, 6(6), 804–813. Lina, R. K., Fratidhina, Y., Trioclarise, R., Puput, G., & Kurniawan, D. (2022). Implementation of sustainable aerobic exercise programs aimed at improving fitness and quality of life in elderly groups in Jatirahayu, Pondok Melati District, Bekasi City. Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 1(1), 23–29. Subekti, R. T., & Nina, R. (2022). The influence of elderly exercise on sleep quality in the elderly. Jurnal Kesehatan Panca Bhakti Lampung, 10(2), 110–120. Retrieved from https://www.ejournal.pancabhakti.ac.id/index.php/jkpbl/article/view/132 Hartono, A. (2023). Statistics of the Aging Population 2023. Badan Pusat Statistik. Retrieved from https://www.bps.go.id/id/publication/2023/12/29/d308763ac29278dd5860fad/statistics-of-aging-population-2023.html Nurdianningrum, B., & Purwoko, Y. (2016). The influence of elderly exercise on sleep quality in the elderly. Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 5(4), 587–598. Retrieved from https://ejournal3.undip.ac.id/index.php/medico/article/view/14255 Späth-Schwalbe, E., Hansen, K., Schmidt, F., Schrezenmeier, H., Marshall, L., Burger, K., et al. (1998). Acute effects of recombinant human interleukin-6 on endocrine and central nervous sleep functions in healthy men. Journal of Clinical Endocrinology and Metabolism, 83(5), 1573–1579. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/9589658 Melancon, M. O., Lorrain, D., & Dionne, I. J. (2014). Exercise and sleep in aging: Emphasis on serotonin. Pathologie Biologie (Paris), 62(5), 276–283. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/25104243